The requirements of a specialist breast centre. (June 2020) - Biganzoli, Laura; Cardoso, Fatima; Beishon, Marc; Cameron, David; Cataliotti, Luigi; Coles, Charlotte E.; Delgado Bolton, Roberto C.; Trill, Maria Die; Erdem, Sema; Fjell, Maria; Geiss, Romain; Goossens, Mathijs; et al.
Abstract: This article is an update of the requirements of a specialist breast centre, produced by EUSOMA and endorsed by ECCO as part of Essential Requirements for Quality Cancer Care (ERQCC) programme, and ESMO. To meet aspirations for comprehensive cancer control, healthcare organisations must consider the requirements in this article, paying particular attention to multidisciplinarity and patient-centred pathways from diagnosis, to treatment, to survivorship. The centrepiece of this article is the requirements section, comprising definitions; multidisciplinary structure; minimum case, procedure and staffing volumes; and detailed descriptions of the skills of, and resources needed by, members and specialisms in the multidisciplinary team in a breast centre. These requirements are positioned within narrative on European breast cancer epidemiology, the standard of care, challenges to delivering this standard, and supporting evidence, to enable a broad audience to appreciate the importance of establishing these requirements in specialist breast centres.